RBP-Tar – a searchable database for experimental RBP binding sites [version 3; peer review: 1 approved, 2 approved with reservations] - Panagiotis Alexiou; David Cechak; Radka Svobodova; Tomas Racek; Vlastimil Martinek; Katarina Gresova (F1000Research)
Background RNA-binding proteins (RBPs) play a critical role in regulating gene expression by binding to specific sites on RNA molecules. Identifying these binding sites is crucial for understanding the many functions of RBPs in cellular function, development and disease. Current experimental methods for identifying RBP binding sites, such as ultra-violet (UV) crosslinking and immunoprecipitation (CLIP), and especially the enhanced CLIP (eCLIP) protocol, were developed to identify authentic RBP binding sites experimentally. Methods To make this data more accessible to the scientific community, we have developed RBP-Tar (https://ncbr.muni.cz/RBP-Tar ), a web server and database that utilises eCLIP data for 167 RBPs mapped on the human genome. The web server allows researchers to easily search and retrieve binding site information by genomic location and RBP name. Use case Researchers can produce lists of all known RBP binding sites on a gene of interest, or produce lists of binding sites for one RBP on different genomic loci. Conclusions Our future goal is to continue to populate the web server with additional experimental datasets from CLIP experiments as they become available and processed, making it an increasingly valuable resource for the scientific community.